Factors associated with physical activity of children and adolescents : a parental point of view - Katainen, Annukka (2020)
Inactivity is a global trend that causes high costs for societies. Even children are engaged in a sedentary lifestyle from the early age even though physical activity has many positive effects on individual’s health. To increase children’s physical activity level, it is important to understand factors associated with physical activity behavior. The aim of the study was to investigate from parental point of view how different factors and parental correlates are related with physical activity of children and adolescents in Finland. Specifically the aim was to find out how parental socio-demographic factors (gender, income level, residential area, education level), parental role modeling, and parental support (instrumental behavior, encouragement, modeling, support/influence) were related with the number of hobbies of the child, hours spent on organized and recreational physical activities, and whether the child was practicing individual or team sports. In addition, a correlation between parental physical activity and child’s physical activity was investigated. Furthermore, an association between children’s gender, age and physical activity was checked.